EXPOSURE TESTS OF SURFACE TREATED SAWN COCONUT TIMBER - R.N. Palomar; P. Jensen; V.K. Sulc (International Coconut Community, 1989)
An investigation was made to determine the relative performance of three readily available inorganic chemicals containing either copper or chromium when applied singly or in combination to sawn coconut timber surfaces. The treating solutions, consisting of chromic acid (H2CrO4) sodium chromate (Na2CrO4) and copper sulphate (CuSO4), were applied by trush to wood surfaces with one coating at the rate of approximately 155 grams per square meter. The specimens were exposed outdoors on racks inclined at 450 angle and facing south. Results after 3 years of test showed that treatments with mixture of H2CrO4 and CuSO4 or combination of Na2CrO4 and CO4 performed better than single application of either H2Cr4 or Na2CrO4. The former treatments still showed uniform and pleasing appearance after the exposure period.